Molluscum Contagiosum Profile At The Dermatology And Venereology Polyclinic Of Prof. I.G.N.G. Ngoerah Central General Hospital Denpasar - Indry Salonika Sutiawan; I Gusti Ayu Agung Praharsini; Adelia Martalova AJ; Alfred Setyono; Putu Akopita Devi; Ni Kadek Setyawati (Green Publisher Indonesia, 2024)
Molluscum contagiosum (MC) is a viral infectious disease caused by the Molluscum Contagiosum Virus (MCV). There are four subtypes of MCV (MCV-1, MCV-2, MCV-3, and MCV-4). The worldwide incidence of MK infection is estimated to be around 2% to 8%, while in the HIV/AIDS population, it is approximately 5% to 18%. To date, there is limited research reporting on the profile of MC patients in Indonesia. This is a descriptive cross-sectional research design. Data were obtained retrospectively and collected from the medical records of patients with molluscum contagiosum who visited the Dermatology and Venereology Polyclinic at Prof. I.G.N.G. Ngoerah General Hospital in Denpasar, Bali, from January 2018 to December 2020. In this study of molluscum contagiosum infection at the Dermatology and Venereology Polyclinic of Sanglah General Hospital in Denpasar, Bali, during the period of January 2018 to December 2020, the majority of participants were aged between 18-44 years (61.1%) and were male (61.1%). Most participants were from Bali (77.8%) and were married (55.6%). Moreover, the majority of participants were sexually active (77.8%) and had a negative HIV status (55.6%). Concerning sexual orientation, most participants identified as heterosexual (83.3%). Regarding the type of therapy received, most participants underwent enucleation (55.5%) and combination therapy (22.2%). Broad public education, especially for parents, regarding molluscum contagiosum should be enhanced to support more effective healthcare efforts encompassing treatment, prevention, and health promotion.